KAJIAN YURIDIS PIDANA TUTUPAN PERSPEKTIF HERMENEUTIKA DOUBLE MOVEMENT - Nasrullah Nasrullah (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2019)
Article 10 of the Criminal Code explains that the Basic Punishment types consisting of capital punishment, imprisonment, confinement, fines, and penalty closure. All the types of punishment have been regulated in the KUHP, except regulations related to penalty closure. The penalty closure is regulated under the act number 20 years 1946 about Closing Penalty. The act is created after the event of July 3rd 1946. A closing penalty requirement is an act that is motivated by intentions that deserve respect. Moreover, the maximum sentence of closing penalty only applies 1 (one) time since the promulgation. Based on the explanation above, to regulate criminal proceedings in the future, it is necessary to analyze criminal closure using the Hermeneutic Double Movement by Fazlur Rahman's theory and the legislation methodology approach, case approaches, and historical approaches. Based on the results of this research, it concludes thatin the future, there should be no need for closing penalties because the meaning of the actions that are motivated by intent that deserves respect is to defend the nation. According to the Hermeneutic Double Movement theory conveyed by Fazlur Rahman, that the act of defending the homeland and the nation does not have the same moral ideas as the previous event, causing the blurring of norms and will be difficult in its application.Keywords: penalty closure, moral ideas, Hermeneutics Double Movement